TORCH INFECTIONS DIAGNOSIS AND TREATMENT METHODS OF TOXOPLASMOSIS - Ra’no Sh. Boltayeva; Nargiza Q. G’ulomjonova; Boburjon Z. Tursunov; Hamidaxon O. Ismatullayeva (Central Asian Journal of Medicine, 2024)
TORCH infections refer to a group of interrelated infectious diseases that pose significant risks during pregnancy, among which toxoplasmosis holds particular importance. Toxoplasmosis is an infection caused by the Toxoplasma gondii parasite, primarily transmitted from animals to humans. This article discusses modern diagnostic methods used to identify toxoplasmosis, the risks it poses during pregnancy, and the importance of timely treatment. Detailed information is provided on serological tests, PCR methods, and other diagnostic approaches. Furthermore, treatment options, including the efficacy of antibiotics and antiparasitic drugs, are analyzed. The article reviews clinical recommendations, preventive measures, and the necessity of early diagnosis during pregnancy. The presented information aims to equip readers with the knowledge and approaches needed to reduce the impact of toxoplasmosis and combat it effectively.